2020
DOI: 10.3390/microorganisms8050755
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compound Screening Using HS-SPME-GC/MS on Saccharomyces eubayanus Strains under Low-Temperature Pilsner Wort Fermentation

Abstract: The recent isolation of the yeast Saccharomyces eubayanus has opened new avenues in the brewing industry. Recent studies characterized the production of volatile compounds in a handful set of isolates, utilizing a limited set of internal standards, representing insufficient evidence into the ability of the species to produce new and diverse aromas in beer. Using Headspace solid-phase microextraction followed by gas chromatography-mass spectrometry (HS-SPME-GC-MS), we characterized for the first time the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 49 publications
(100 reference statements)
0
40
0
Order By: Relevance
“…This issue in Microorganisms aims to contribute to the update of knowledge regarding yeasts, regarding both basic and also applied aspects. Among the great contributions to this issue we have a manuscript devoted to the brewing industry and the recent isolation of the yeast Saccharomyces eubayanus [24]. The use of headspace solid-phase microextraction followed by gas chromatography-mass spectrometry (HS-SPME-GC-MS) has contributed to the production of volatile compounds in wild strains and to compare them to a commercial yeast.…”
Section: Special Issue On "Yeast Fermentation"mentioning
confidence: 99%
“…This issue in Microorganisms aims to contribute to the update of knowledge regarding yeasts, regarding both basic and also applied aspects. Among the great contributions to this issue we have a manuscript devoted to the brewing industry and the recent isolation of the yeast Saccharomyces eubayanus [24]. The use of headspace solid-phase microextraction followed by gas chromatography-mass spectrometry (HS-SPME-GC-MS) has contributed to the production of volatile compounds in wild strains and to compare them to a commercial yeast.…”
Section: Special Issue On "Yeast Fermentation"mentioning
confidence: 99%
“…Since PAB is a fermentation product, its main organoleptic characteristics are affected to a large extent by fermentation and especially by the microorganisms used, as was also proved in several fermented beverages made from red dragon fruit [ 5 ], diluted honey [ 6 ], Pilsner wort [ 7 ], apple juice [ 8 ] and grape juice [ 9 ]. Several studies reported that fermentation of pomegranate juice resulted in a completely new product with altered bioactive components, mainly due to reactions of polymerization, condensation, oxidation, hydrolysis, enzyme activity, and interactions of antioxidants with yeast cell walls [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fermentations were carried out as previously described [28,29]. Briefly, fermentations were performed in at least three biological replicates, depending on the experiment, in 12 °P using a BrewFerm Pilsner commercial beer kit (Beringen, Belgium).…”
Section: Fermentations In Beer Wortmentioning
confidence: 99%
“…At the end of the fermentation, metabolites such as glucose, fructose, maltose, maltotriose, ethanol and glycerol were estimated using HPLC [27]. Volatile compounds were detected using HS-SPME-GC-MS as previously described [28].…”
Section: Fermentations In Beer Wortmentioning
confidence: 99%
See 1 more Smart Citation